Innovative adaptation of coagulation-sedimentation-filtration process in lightly polluted urban rivers with seasonal high turbidity - Yujie Yuan; Tao Zhang; Yaqian Zhao; Yuan Liu; Song He; Yamei Cai; Yuanbo Liu; Shu Wang (Scientific Reports)
Abstract Urban rivers, as essential components of ecosystems, have endured severe pollution as a consequence of rapid urbanization and economic development. However, the dynamics of pollution and turbidity in urban rivers within residual red clay alluvial plains remain poorly understood, and there is an urgent need for effective engineering strategies focused on pollution control and turbidity management to improve water quality and restore ecosystem functions. This study endeavored to investigate the spatiotemporal mapping of water quality and corresponding treatment strategy for a slow-flowing urban river with lightly-pollution and seasonal high turbidity within the alluvial plain of southern China. Results from 10 sampling events showed the average concentrations of COD (15.13–22.00 mg/L), NH3-N (1.15–11.70 mg/L), and TP (0.14–0.26 mg/L), corresponding to Class III–V of China’s environmental quality standards for surface water (EQSSW). Annual water transparency ranged from 25 cm to 30.5 cm, although the average value of SS was only in the range of 6.0 mg/L to 24.5 mg/L. Notably, it presented significant spatiotemporal heterogeneity and frequently exceeded the standard. A total of 28 group field pilot scale in-situ tests of the coagulation-sedimentation-filtration process exhibited a highly satisfactory treatment performance on turbidity and TP. The optimal dosages of polyaluminium chloride (PAC) and polyacrylamide (PAM) were determined to be 50 ppm and 1.5 ppm, respectively. The treatment process achieved exceptional removal efficiencies of 99.53% for turbidity and 94.69% for TP, producing effluent with stabilized turbidity < 1 NTU and TP concentrations as low as 0.017 mg/L, fully compliant with Class II for EQSSW. Furthermore, the system was capable of adapting to flow variations during the rainfall events by adjusting the surface load. These findings are of great significance for the in-depth comprehension of urban river pollution dynamics in the plain area and provide effective scientific and technological support for the remediation of such lightly-polluted river with high turbidity.